Calcium and phsophorus Requirements of Caged Layers - Brahma T C (Department of Poultry Science, College of Veterinary and Animal Science, 1986)
A 4 x 4 factorial arrangement to determine the dietary requirements of calcium and phosphorus for caged layers under the hot-humid agro-climatic conditions of Kerala is presented in this thesis. Two hundred fifty six single comb White leghorn strain cross pullets (IWN x IWP ) of the Mannuthy Centre of AICRP on Poultry foe eggs formed the experimental birds. The birds were randomly assigned to 16 dietary calcium-phosphorus combination groups. The dietary calcium levels employed were 2.50, 3.00, 3.50 and 4.00 per cent and that of phosphorus levels wee 0.50 , 0.60, 0.70 and 0.80 percent the observations of the experiment were recorded over 10,28 day – periods The percent hen-day egg production and feed efficiency (both on egg number and egg mass) were significantly (P < 0.01) superior in birds fed 4.00 percent dietary calcium. The dietary levels of phosphorus had not exerted any influence on hen-day egg production and feed efficiency. The feed intake and egg weight were not influenced either by the dietary levels of calcium or phosphorus or both. The egg shell quality (specific gravity and shell thickness ) was significantly (P < 0.01 ) better in egg laid by hens fed 3.50 and 4.00 percent dietary calcium. The percent egg shell was significantly (p< 0.01) highest with 3.50 percent calcium. However, percent egg shell between 3.50 and 4.00 percent dietary calcium was not statistically different. The egg shell quality (specific gravity, shell thickness and percent shell) was significantly (P< 0.01) poorest with 2.50 percent calcium diet. The dietary phosphorus levels had not exerted any significant influence on egg shell quality (specific gravity, shell thickness and percent shell). The serum calcium level, serum inorganic phosphorus level and percent tibia ash were not influenced by the levels of dietary calcium and phosphorus . The serum alkaline and acid phosphatase levels did not give any clue as to the adequacy of the dietary calcium and phosphorus level employed. The calcium intake was higher with higher levels of dietary calcium. There was a trend of increased absolute calcium retention as the calcium level in the diets increased but it was not statistically significant. Dietary phosphorus levels positively improved absolute retention calcium. The mortality among birds were nit suggestive of any influence due to dietary calcium and phosphorus. The results of experiments revealed that in terms of any of the major economic traits used for evaluating the dietary calcium adequacy of caged layers, 4.00 percent calcium was found to be superior over the other levels. In respect of dietary phosphorus, the levels of 0.50 per cent seems to be adequate but the absolute retention of phosphorus was negative at this level of incorporation irrespective of calcium levels. Therefore, it will be more logical to set the requirements of dietary phosphorus at 0.60 per cent than at 0.50